Effect of denture cleansers on color stability, surface roughness, and hardness of different denture base resins - Anand Porwal; Meenakshi Khandelwal; Vikas Punia; Vivek Sharma (Wolters Kluwer Medknow Publications, 2017)
Aim: The purpose of this study was to evaluate the effect of different denture cleansers on the color stability, surface hardness, and roughness of different denture base resins. Materials and Methods: Three denture base resin materials (conventional heat cure resin, high impact resin, and polyamide denture base resin) were immersed for 180 days in commercially available two denture cleansers (sodium perborate and sodium hypochlorite). Color, surface roughness, and hardness were measured for each sample before and after immersion procedure. Statistical Analysis: One-way analysis of variance and Tukey's post hoc honestly significant difference test were used to evaluate color, surface roughness, and hardness data before and after immersion in denture cleanser (α =0.05). Results: All denture base resins tested exhibited a change in color, surface roughness, and hardness to some degree in both denture cleansers. Polyamides resin immersed in sodium perborate showed a maximum change in color after immersion for 180 days. Conventional heat cure resin immersed in sodium hypochlorite showed a maximum change in surface roughness and conventional heat cure immersed in sodium perborate showed a maximum change in hardness. Conclusion: Color changes of all denture base resins were within the clinically accepted range for color difference. Surface roughness change of conventional heat cure resin was not within the clinically accepted range of surface roughness. The choice of denture cleanser for different denture base resins should be based on the chemistry of resin and cleanser, denture cleanser concentration, and duration of immersion.